The Aesthetics of Stones - Anna Petronella Foultier (ESPES)
In this paper, I shall examine the aesthetic experience afforded by stones – in particular the kind of smoothly rounded enchanting pebbles that invite us to handle and collect them – and argue that it is not simply an experience of natural objects, but that their appeal is related to their being comparable to artefacts, although the workmanship was enacted not by a human but by superhuman forces. Such stones have, as it were, an ontological position between natural aesthetic phenomena and artefacts and summons us to connect with our earthly origins. Finding a stone that is not only pleasing to the eye but more importantly to the hand can bring one into contact with the planet’s deep past. I explore the affinities between stones and Korsmeyer’s (2019) “Real Things” – rare, old or singular artefacts, characterised by genuineness and a distinct aura, that invite us to come closer to and touch them.